Sporadic Creutzfeldt–Jacob Disease: A case report: Sporadična Creutzfeldt-Jacobova bolezen – prikaz primera - Mandjikoska, Sonja; Horvat Pinterić, Gordana (Acta Medico-Biotechnica, 2021)
Purpose: Creutzfeldt–Jacob Disease (CJD) is a rare progressive neurodegenerative disorder and the most common form of prion disease. CJD is categorized into four subtypes: sporadic (sCJD), familial, iatrogenic, and variant. The clinical presentation of sCJD is characterized by progressive dementia, myoclonus, visual disturbances, cerebellar ataxia, and pyramidal and/ or extrapyramidal signs. Diagnosis is based on clinical presentation, and the results of an electroencephalogram, cerebrospinal fluid analysis, and cranial magnetic resonance imaging.Case Report: The case of an 81-yearold woman with progressive dementia and typical electroencephalogram and magnetic resonance imaging findings for sporadic is presented.Conclusion: No single diagnostic test for sCJD is available. In suspected sCJD, the first priority is to exclude treatable forms of dementia, such as encephalitis or chronic meningitis.